Molecular and phylogenetic analysis of HIV-1 variants circulating in Italy - Sbreglia Costanza; Casoli Claudio; Pilotti Elisabetta; Re Maria; Vitone Francesca; Tagliamonte Maria; Petrizzo Annacarmen; Buonaguro Luigi; Perrella Oreste; Tornesello Maria; Buonaguro Franco M (Infectious Agents and Cancer, 2008)
Abstract Objective The continuous identification of HIV-1 non-B subtypes and recombinant forms in Italy indicates the need of constant molecular epidemiology survey of genetic forms circulating and transmitted in the resident population. Methods The distribution of HIV-1 subtypes has been evaluated in 25 seropositive individuals residing in Italy, most of whom were infected through a sexual route during the 1995–2005 period. Each sample has been characterized by detailed molecular and phylogenetic analyses. Results 18 of the 25 samples were positive at HIV-1 PCR amplification. Three samples showed a nucleotide divergence compatible with a non-B subtype classification. The phylogenetic analysis, performed on both HIV-1 env and gag regions, confirms the molecular sub-typing prediction, given that 1 sample falls into the C subtype and 2 into the G subtype. The B subtype isolates show high levels of intra-subtype nucleotide divergence, compatible with a long-lasting epidemic and a progressive HIV-1 molecular diversification. Conclusion The Italian HIV-1 epidemic is still mostly attributable to the B subtype, regardless the transmission route, which shows an increasing nucleotide heterogeneity. Heterosexual transmission and the interracial blending, however, are slowly introducing novel HIV-1 subtypes. Therefore, a molecular monitoring is needed to follow the constant evolution of the HIV-1 epidemic.